Generalization in context sensitive grammars - PLUCIŃSKI, Andrzej (Archives of Acoustics, 2007)
An alternative to the recognition systems used so far can be systems based on context sensitive grammars. A precondition for success will be an implementation with great capacity for generalization. We propose three methods of generalization based on the assumption that similar stimuli invoke similar or identical reactions.